PENERAPAN INDEKS GINI UNTUK MENGINDENTIFIKASI TINGKAT PEMERATAAN PENDAPATAN DAN PENGELUARAN RUMAH TANGGA PEDESAAN DI WILAYAH JAWA DAN BALI - OKA ADNYANA, MADE; NUR SUHAETI, RITA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003)
Gini Index application to identify rural income and expenditure distributions in Java and Bali Areas. Rural household welfare can be approached by evaluating income ad expenditure level both for total and capita level. In the mean time, income structure reflects activity distribution as sources of income gained by the households. Income distribution level can be identified by applying Gini Index. This study was conducted in various agro-ecosystems in Java and Bali. This paper discusses about income and expenditure structures of those rural households at the mentioned agro-ecosystems. This study results was expected to be useful for research and assessment (R&A) in those areas mainly in evaluating outcome and impact of the R&A in those respective agro-ecosystems.
Keywords: Income, Expenditure, Household, Gini Index, Agro-Ecological Zone (AEZ)